2017
DOI: 10.1038/srep44324
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide gramicidin S is accumulated in granules of producer cells for storage of bacterial phosphagens

Abstract: Many antimicrobial peptides are synthesized non-ribosomally in bacteria, but little is known about their subcellular route of biosynthesis, their mode of intracellular accumulation, or their role in the physiology of the producer cells. Here, we present a comprehensive view on the biosynthesis of gramicidin S (GS) in Aneurinibacillus migulanus, having observed a peripheral membrane localization of its synthetases. The peptide gets accumulated in nano-globules, which mature by fusion into larger granules and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 34 publications
(58 reference statements)
1
14
0
Order By: Relevance
“…This intrinsic cell-uptake activity has already been explored in eukaryotic cells to specifically target mitochondria with GS derivatives 64 . In the context of prokaryotic cells, together with the ability to bind certain nucleotides and small phosphorylated molecules 2933 , GS thus seems to be capable of effectively inhibiting bacterial stress response and biofilm development in a fashion previously attributed to IDR. The periplasmic and intracellular binding of anionic phosphorylated metabolites by GS should deplete their levels, and therefore inhibit metabolic activity and possibly even affect gene regulation, e.g., due to interference with phosphorylation in signal transduction processes.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This intrinsic cell-uptake activity has already been explored in eukaryotic cells to specifically target mitochondria with GS derivatives 64 . In the context of prokaryotic cells, together with the ability to bind certain nucleotides and small phosphorylated molecules 2933 , GS thus seems to be capable of effectively inhibiting bacterial stress response and biofilm development in a fashion previously attributed to IDR. The periplasmic and intracellular binding of anionic phosphorylated metabolites by GS should deplete their levels, and therefore inhibit metabolic activity and possibly even affect gene regulation, e.g., due to interference with phosphorylation in signal transduction processes.…”
Section: Discussionmentioning
confidence: 91%
“…Citrate phosphate dextrose-stabilized human erythrocyte suspensions were obtained from Karlsruhe Municipal Hospital. The washed 0.25% suspension of erythrocytes were incubated with peptides at 37 °C for 30 min as described earlier 33 . The mixture was pelleted (13 000 rpm, 10 min, 4 °C), and the absorbance of the supernatant was recorded at 540 nm vs. reaction buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The high cytotoxicity of peptide-based biomaterials towards mammalian cells is a major limitation for the development of AMPs as therapeutics. GS not only has great antimicrobial activity, but it is also highly toxic towards mammalian cells, which is attributed to its amphiphilic structure that causes it to lack selectively in its affinity for cellular membranes [35]. In this study, OIR3, IR3 and DIR3, which each have three IR repeating units, demonstrated no hemolytic activity towards erythrocytes (Table 1) and only weak toxicity towards RAW264.7 cells (Figure 2B), while GS had high toxicity towards mammalian cells, similar to that found previously, suggesting that the simplified, engineered active peptides had a great selectivity for negatively charged bacterial membranes versus zwitterionic mammalian cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, gramicidin S, a small cyclic peptide, synthesized by Bacillus brevis, is an important and powerful antibiotic, effective against a variety of Gram-positive and Gram-negative bacteria (M. BERDITSCH & al [45]; J.W. LIOU & al [46]).…”
Section: Non-ribosomally Biosynthesized Peptidesmentioning
confidence: 99%